The mediating role of knowledge management processes in the development of organizational innovation in the public sector - ‎Naghavi, M.; Dastaviz, A.H.; Jamshidy, M. (Asian Network for Scientific Information, 2013)
The aim of this study was to examine the relationships among organizational factors, knowledge management processes ‎and organizational innovation. In addition, the role of knowledge management processes as mediator in the development ‎of organizational innovation also was investigated, In this study, four research questions and 25 hypotheses were ‎examined, The population of this study was heads of supervisory departments of the public banks' branches in all of the ‎Iran provinces A questionnaire containing 42 questions with a likert-type scale from I (strongly disagree) to 5 (strongly ‎agree) was used as the rnam instrument in gathenng data and a total of 229 respondents were involved in the survey, As ‎an analytical method, Structural Equation Modeling was selected using AJ\.fOS 16.0 version. The findings of this study ‎identified the mediating role of knowledge management processes ill the relationship between organizational factors and ‎organizational innovation. Results of the Structural Equation Modeling analysis also revealed that "IT support" of ‎organizational factors has the highest contribution toward the prediction of organizational irmovation and so, the ‎incentives and leadership of organizational factors were the second and third predictor variables of organizational ‎innovation, respectively. From an academic point of view, the results of this study especially its intermediate linkage helps ‎scholars understand the processes further, which might be helpful in discovering additional mediator at different levels of ‎analysis‎